Pemakzulan Presiden di Indonesia Studi Putusan Final dan Mengikat Oleh Mahkamah Konstitusi Untuk Menciptakan Kepastian Hukum - Uci Sanusi (UIN Sunan Kalijaga Yogyakarta, 2018)
The Constitutional Court of the state institutionformed in the Third Amendment of the 1945Constitution has 4 (four) authorities and one obligation.The obligation of the Constitutional Court is to decidethe opinion of the DPR on alleged violations of lawcommitted by the President / or Vice President asstipulated in Article 7A and 7B of the 1945 Constitution.If the Constitutional Court confirms the opinion of theDPR, then the DPR will conduct a plenary session toproceed to the People's Consultative Assembly as thefinal breaker for impeachment, but the People'sConsultative Assembly may be able to disobey theConstitutional Court's ruling which has justified theopinion of the House of Representatives because thereare no rules that stipulate that the Constitutional Courtis final and binding for the People's ConsultativeAssembly so that The MPR did not comply with theConstitutional Court's decision so that it could causethe legal certainty